2020
DOI: 10.1111/ajco.13385
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of treatment‐related adverse events of programmed cell death‐1 and its ligand‐1 inhibitors in different cancer types: A meta‐analysis and systemic review of clinical trials

Abstract: Programmed cell death receptor-1 and its ligand-1 (PD-1/PD-L1) inhibitors have been applied to many cancers, but the difference of treatment-related adverse events (AEs) across cancer types remains unknown. We performed a meta-analysis and systemic review to compare the incidences of commonly reported all-grade AEs across cancer types and found that the most frequent AEs were fatigue, rash/pruritus, loss of appetite/nausea and diarrhea. However, each cancer type also had its higher incidences of AEs involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 118 publications
2
5
0
Order By: Relevance
“…AEs and complications occurred in this study at a similar frequency to those reported in the published data on neoadjuvant chemotherapy (15). In this study, we found that immune-related AEs could be well monitored and managed (16), which is similar to the observations made in the NADIM study (17). Only in 1 case did neoadjuvant therapy need to be halted after 1 cycle of treatment, with this patient's complication being lung abscess caused by obstructive pneumonia, which was unrelated to PD-1 inhibitor treatment.…”
Section: Discussionsupporting
confidence: 87%
“…AEs and complications occurred in this study at a similar frequency to those reported in the published data on neoadjuvant chemotherapy (15). In this study, we found that immune-related AEs could be well monitored and managed (16), which is similar to the observations made in the NADIM study (17). Only in 1 case did neoadjuvant therapy need to be halted after 1 cycle of treatment, with this patient's complication being lung abscess caused by obstructive pneumonia, which was unrelated to PD-1 inhibitor treatment.…”
Section: Discussionsupporting
confidence: 87%
“…However, the incidence of irAEs varies according to different ICIs. In addition, the incidence of irAEs is also higher in patients who received combined immunotherapy than monotherapy (26,27). In this study, the irAE incidence for the 21 patients who were treated with ICI monotherapy was 42.8%, with mainly mild to moderate clinical manifestation of thyroid dysfunction.…”
Section: Discussionmentioning
confidence: 61%
“…Gu et al. ( 85 ) found an increased likelihood of hypothyroidism after PD-1 inhibition against lung cancer, and renal injury for PD-L1. Pneumonitis was more common following PD-1 treatment, but hepatitis, rash and lipase elevation were more common for PD-L1.…”
Section: Discussionmentioning
confidence: 99%